2011
DOI: 10.1089/neu.2010.1413
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Intrathecal Catheter Delivery of Bone Marrow Mesenchymal Stromal Cells Improves Functional Recovery in a Rat Model of Contusive Spinal Cord Injury

Abstract: Transplantation of bone marrow mesenchymal stromal cells (MSCs) has been shown to improve the functional recovery in various models of spinal cord injury (SCI). However, the issues of the optimal dose, timing, and route of MSC application are crucial factors in achieving beneficial therapeutic outcomes. The objective of this study was to standardize the intrathecal (IT) catheter delivery of rat MSCs after SCI in adult rats. MSCs labeled with PKH-67 were administered by IT delivery to rats at 3 or 7 days after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 52 publications
4
57
0
Order By: Relevance
“…30,[51][52][53][54][55] Some of the beneficial effects of MSCs are mediated by their release of neurotrophic factors. 34,35 This allows neurotrophins to be delivered locally to the spinal cord, overcoming issues related to neurotrophin penetration and bioavailability.…”
Section: Beneficial Effects Of Mscsmentioning
confidence: 99%
“…30,[51][52][53][54][55] Some of the beneficial effects of MSCs are mediated by their release of neurotrophic factors. 34,35 This allows neurotrophins to be delivered locally to the spinal cord, overcoming issues related to neurotrophin penetration and bioavailability.…”
Section: Beneficial Effects Of Mscsmentioning
confidence: 99%
“…Because the i. With respect to the timing of the injection, Cizkova et al 6 reported the interesting finding of significantly greater motor functional recovery after 3 daily injections of a total 1.5 × 10…”
Section: 10mentioning
confidence: 99%
“…The IT implantation of the catheter was performed according to our previously published procedure (Cizkova et al 2010;Hayes et al 2003). The rats were anesthetized with 1.5-2% halothane and the posterior scalp was incised (2-3 cm) in the midline and the muscles were gently separated.…”
Section: Implantation Of Intrathecal Cathetermentioning
confidence: 99%